Multidimensional characteristics of sporting potential of young handball players - Filipino Coelho, Emerson (2023)
BACKGROUND: Assessing the sporting potential of young athletes is an important task for coaches. The attempt to quantify the “coach’s eye” has been a major challenge for researchers. OBJECTIVE: The aim of this study was to compare multidimensional indicators of sporting talent in young handball players classified as high and low sporting potential, according to the coach’s opinion. METHODS: 22 handball athletes aged 15 to 17 from a Federal Education Institute participated. The sporting potential was evaluated by the team coach, on a scale from one to five, classifying the athletes into two groups: high potential (n=11) and low potential (n=11). The following were evaluated: sports experience, body mass, height, sitting height, hands length, wingspan, skinfolds, speed, agility, handgrip, vertical jump, flexibility, aerobic resistance, coping skills, motivation, perceived competence, socioeconomic status, biological maturation, dribbling and tactical skills. RESULTS: High-potential handball players, when compared to low-potential ones, were faster (p=0.05), more agile (p=0.02) and stronger (p=0.02), more experienced (p=0.05), showed greater perceived competence (p=0.01), competitiveness (p=0.02) and better dribbling performance (p=0.05) and tactical skills (p=0.03). CONCLUSION: The handball players evaluated by the coach as having high sporting potential were those who had better physical-motor performance, higher level of psychological, technical and tactical skills when compared to low potential athletes.